Effect of compost as soil amendment on growth, yield and quality of okra (Abelmoschus esculentus L. Moench) - Amissah, Ransford (University of Cape Coast, 2015)
Organic nutrient sources such as compost could be used to improve the low fertility of tropical soils as it has the potential to enhance soil physical, chemical and biological properties and improve growth, yield and quality of crops. Pot and field experiments were conducted to investigate the effect of compost on growth, yield and nutritional quality of okra, Abelmoschus esculentus (L.) Moench. The pot experiment was done using the Completely.Randomized design while field trial was done in Split-Plot Design (SPD). In all the pot and field experiments, compost was incorporated at rates of 0 kg N ha-1 (control), 100 kg N ha-1 and 200 kg N ha-1 with three replicates. Asontem and Enidaso okra varieties were used as test crops. Results from the study indicated that the addition of compost at 100 kg N ha-1 in the pot experiment showed significantly greater plant height, number of leaves, leaf area, dry matter content and nutrient content in stem, leaf, petiole and root of harvested okra plants. The results for field work showed that the Enidaso variety responded better to compost application in that this variety recorded the highest plant height, had less incidence of okra mosaic disease and had higher dry matter. Using the Duncan’s Multiple Range Test (DMRT), no significant difference was found between compost application rates of 100 kg N ha-1 and 200 kg N ha-1 in terms of soil organic carbon, soil total nitrogen,available phosphorus, pH, ECEC, moisture content, exchangeable Ca2+ and Mg2+ contents. Proximate analysis for moisture and protein contents as well as nutrients (magnesium, potassium, phosphorus and sodium) composition of edible pods of okra was also not significant. For economic reasons, an application rate of 100 kg N ha-1 was recommended.
xv,182p.:ill
Keywords: Tropical soils; Organic nutrient; Abelmoschus esculentus L. Moench; okra; Soil amendment; Compost